Investigating Malaysian students’ e-learning experiences with Massive Open Online Courses (MOOCs) / Safwana Nur Widad Safri - Safri, Safwana Nur Widad (2023)
The Ministry of Education (MOE) of Malaysia has identified e-learning as an integral component of higher education and lifelong learning. However, the emergence of Massive Open Online Courses (MOOCs) and the development of various delivery systems for these courses have raised concerns about the quality of education. The new challenges in online education are characterised by the increased focus on users’ reactions and fast-changing needs. Furthermore, because of the restricted availability of face-to-face (F2F) interaction and access between instructors and students, MOOCs have limited interaction and access between instructors and students. In particular, this study focuses on applying a hierarchical model to identify the dimensions of elearning service quality as perceived by undergraduate students at public universities in Malaysia. The proposed research framework adapted the hierarchical and multidimensional model that Brady and Cronin (2001) developed, with modifications to make it more appropriate for MOOCs in Malaysia. The UiTM MOOC was chosen as the study setting focusing on the programme the Faculty of Hotel and Tourism Management (FHTM) offered. The undergraduate students are able to learn theories and practical skills such as housekeeping, pastry, and culinary through the UiTM MOOCs. Using convenience sampling, online questionnaires were distributed to students who have experience learning hospitality, culinary, and tourism courses through FHTM MOOC on the OpenLearning platform. Four-hundred and eighty-two responses were obtained from the data collection process. The data were analysed by using the structural equation modelling assessment. The hierarchical factor structure, including the e-Learning Service Quality, consists of four primary dimensions (Physical Environment Quality, Interaction Quality, Learning Quality, and Learning Outcome Quality), used to measure Student Experience and Continuation Intention MOOCs in Malaysia. This study has found that e-Learning Service Quality positively correlates with Student Experience and Continuance Intention. Besides that, only Learning Quality and Learning Outcome Quality have a positive relationship with the Student Experience. In addition, Physical Environment Quality, Learning Quality and Learning Outcome Quality have a positive relationship with Continuance Intention. Additionally, the Student Experience also has a positive relationship with Continuance Intention in MOOC. Meanwhile, based on the findings, Interaction Quality negatively relates to Student Experience and Continuance Intention. This study offers a valuable framework for understanding the interrelationships among e-learning service quality, student experience, and continuance intention in MOOCs